A Randomized Controlled Trial of Teat-Sealant and Antibiotic Dry-Cow Treatments for Mastitis Prevention Shows Similar Effect on the Healthy Milk Microbiome - Biscarini, Filippo; Cremonesi, Paola; Castiglioni, Bianca; Stella, Alessandra; Bronzo, Valerio; Locatelli, Clara; Moroni, Paolo (Frontiers in Veterinary Science, 2020)
Lactating cows are routinely treated at dry-off with antibiotic infusions in each quarter for the cure and prevention of pathogenic intramammary infection, which remains the most common disease in dairy herds. This approach is known as blanket dry-cow therapy, usually effective for the prevention and cure of infections, but has been shown to potentially contribute to the emergence and spreading of antibiotic resistant bacterial strains. Exploring the use of non- antibiotic treatments coupled with selective dry-cow therapy is necessary to reduce the risk of antibiotic resistance and potential interference with milk microbiome balance. The impact of selective dry-cow therapy on the physiological milk microbiome needs to be carefully evaluated. In this small-scale trial, five healthy (no mastits, SCC < 200 000 cells mL −1 ) second-parity cows from dry-off to five days after calving were sampled. For every cow, each quarter received a different treatment: i) bismuth salnitrate (internal teat sealant, OrbSeal) front-right quarter; ii) cephalonium dihydrate (Cepravin , MSD, Italy), rear right quarter; iii) benzathine cloxacillin (Cloxalene dry, Ati, Italy), rear left quarter. No treatment was applied to the remaining quarter (front left) which served as experimental control. For 16S rRNA gene sequencing, bacterial DNA was extracted from 5 ml of milk samples, amplified using the primers for the V3-V4 hypervariable regions and sequenced in one MiSeq (Illumina) run with 2x250-base paired-end reads. Bacteriological results confirmed that the quarters were all healthy. The phyla Proteobacteria, Firmicutes and Actinobacteria were the most abundant for all treatments and controls at all three timepoints, accounting for over 80% of the entire milk microbiota composition. No significant differences were found between treatments and controls in terms of the major alpha and beta diversity indexes, revealing that antibiotic and non-antibiotic treatments for selective dry- cow therapy did not alter significantly the milk microbiome of dairy cows. The milk microbiota composition showed a clear evolution over the lactation cycle, and the overall changes in the milk microbiota diversity over the lactation cycle were mainly independent of treatments.